Higher-Order Poincar e Beams from Lasers - Sroor, Hend (My University, 2019)
Traditional laser systems are usually designed in such a way as to produce the fundamental Gaussian mode. The Gaussian mode, however, is not ideally suitable for all applications at hand, thus presenting the need for structured light modes. These modes have captured great attention due to their unique properties and have found a myriad of applications. Laser modes are often characterised based on intensity measurements to infer, through propagation, the beam quality factor. This detection scheme does not consider the polarisation state of the laser mode. Therefore, it is only e ective for measuring the quality of laser modes with uniform polarisation (scalar modes). Structured modes with non-uniform polarisation, namely vector beams, are usually di erentiated from scalar beams by qualitative measures, for example, visual inspection of beam pro les after a rotating polariser. There is no quantitative measure de nes the quality of a vector mode, i.e. a measure that can tell how vector the beams is. Consequently, there are still many open questions such as: how can we manipulate light's degrees of freedom inside the resonator to control the generation of di erent families of structured light? And how can we detect and characterise these modes? The work presented in this thesis subsequently focuses on laser beam shaping inside solid state resonators. Here we will generate desirable transverse modes of structured light and develop tools to detect them. We consider two approaches for laser beam shaping inside the laser resonator. The rst approach involves using amplitude masking inside unstable canonical resonators to allow controlled generation of a unique family of structured modes known as fractal modes. The second approach involves coupling of light within metasurefaces inside the resonator for the selection of pure higher-order Laguerre-Gaussian modes and superpositions thereof. Subsequent to this, we develop a novel technique to quantitatively identify the purity of structured modes based on their \vectorial" nature. Finally, we investigate how the properties of such beams change when they are ampli ed through birefringent and isotropic amplifiers.
A thesis submitted in ful lment of the requirements for the degree of Doctor of Philosophy in Science in the School of Physics February 2019
Keywords: Resonators; Proton beams; Lasers